Association of Female Menopause With Atrioventricular Mechanics and Outcomes - Sung, Kuo-Tzu; Chandramouli, Chanchal; Lo, Chi-In; Tsai, Jui-Peng; Lai, Yau-Huei; Hsiao, Chih-Chung; Tsai, Shin-Yi; Yun, Chun-Ho; Hung, Ta-Chuan; Kuo, Jen-Yuan; Lin, Jiun-Lu; Hou, Charles Jia-Yin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Despite known sex differences in cardiac structure and function, little is known about how menopause and estrogen associate with atrioventricular mechanics and outcomes. Objective: To study how, sex differences, loss of estrogen in menopause and duration of menopause, relate to atrioventricular mechanics and outcomes. Methods: Among 4051 asymptomatic adults (49.8±10.8years, 35%women), left ventricular (LV) and left atrial (LA) mechanics were assessed using speckle-tracking. Results: Post-menopausal (vs. pre-menopausal) women had similar LV ejection fraction but reduced GLS (20.34±2.00% vs 21.33±1.85%), reduced PALS (34.7±7.9% vs. 40.9±7.4%), increased LA stiffness (0.30±0.14%-1 vs. 0.22±0.10%-1), higher LV sphericity (0.63±0.06 vs. 0.60±0.07) and LV torsion (2.62±1.01°/cm vs 2.14±0.86°/cm, all p<0.001). Increasing years of menopause was associated with reduced GLS, markedly worse LA mechanics despite greater LV sphericity and higher torsion. Lower estradiol levels correlated with more impaired LV diastolic function, impaired LV GLS, greater LA stiffness, and increased LV sphericity and LV torsion (all p<0.05). Approximately 5.1% (34/669) of post-menopausal women experienced composite outcomes (all-cause death and incident heart failure) over 2.9years of follow-up. Greater LV sphericity [adjusted hazard ratio (aHR) 1.04, 95%CI 1.00-1.07], impaired GLS (aHR 0.84, 95%CI 0.74-0.96), reduced PALS (aHR 0.94, 95%CI 0.90-0.99) and higher LA stiffness (aHR 12.4, 95%CI 1.79-85.8) were independently associated with composite outcomes post-menopause. Conclusion: Menopause was associated with greater LV/LA remodeling and reduced LV longitudinal and LA function in women. The cardiac functional deficit with menopause and lower estradiol levels, along with their independent prognostic value post-menopause, may elucidate sex differences in heart failure further.